INTERPRETATION AND IMPLICATION OF DEFAULT BY THE CONSTITUTIONAL COURT RELATED TO THE EXECUTION OF FIDUCIARY - Agung Pitra Maulana (Universitas Surakarta, 2020)
The purpose of this research is to find out how the interpretation of promise injury related to the execution of the object of Fiduciary in the Constitutional Court Decision No. 18 / PUU-XVII / 2019 and to find out what are the implications of the Constitutional Court Decision. The research method in this research is normative legal research. Normative legal research is a process to find legal rules, legal principles, and legal doctrines in order to address legal issues. The result of this research is application for testing Article 15 paragraph (2) and paragraph (3) of Law No. 42/1999 has been decided by Constitutional Court on January 6, 2020. The purpose of this study is to find out how the interpretation of Constitutional Court on meaning of